'Push' and 'Pull' Modeling In RosettaNet's Business-To -Business e-Commerce Partner Interface Processes. - Ting, Tin Tin; Khoo, Vincent, Kay Teong (2007)
This paper analyses and compares the performances of Business-to-Business e-Commerce data quality and service quality among the use of the 'Push' model, the ,pult' model and the 'Push and Pull' model. As in other Business to-Business standard and technologies, the RosettaNet's Partner Interface processes attempt to enhance the business document interchange efficiency, which is a critical success factor among the trading partners in the small and medium-sized industries.